Four views on the spectrum of evangelicalism - Bauder, Kevin T.; Naselli, Andrew David, 1980-; Hansen, Collin, 1981- (Grand Rapids, Mich. : Zondervan, 2011)
"Four Views on the Spectrum of Evangelicalism compares and contrasts four distinct positions on the current fundamentalist-evangelical spectrum in light of the history of American fundamentalism and evangelicalism. Each contributor defines evangelicalism, locates his view in historical context, and discusses how he understands Scripture and its authority. To illustrate the differences, each addresses three issues recently contested within evangelicalism: the question of Christian cooperation illustrated by Evangelicals and Catholics Together and the Manhattan Declaration; the question of doctrinal boundaries raised by open theism, a debate that has shaken denominations, schools, and the Evangelical Theological Society in the 1990s and 2000s; penal substitutionary atonement, a key doctrinal issue related to the gospel. Each author explains his position, which is critiqued by the other three authors. The interactive and fair-minded nature of the Counterpoints format allows the reader to consider the strengths and weaknesses of each view and draw informed, personal conclusions."--Publisher.
Introduction / Collin Hansen -- Fundamentalism / Kevin T. Bauder ; Responses -- Confessional evangelicalism / R. Albert Mohler Jr. ; Responses -- Generic evangelicalism / John G. Stackhouse Jr. ; Responses -- Postconservative evangelicalism / Roger E. Olson ; Responses -- Conclusion / Andrew David Naselli.
Includes bibliographical references and indexes.
Keywords: Evangelicalism; Evangelicalism -- Relations -- Catholic Church; Open theism; Atonement